Icaritin Improves Memory and Learning Ability by Decreasing BACE-1 Expression and the Bax/Bcl-2 Ratio in Senescence-Accelerated Mouse Prone 8 (SAMP8) Mice. (30th June 2020) - Li, Yuan-Yuan; Huang, Nan-Qu; Feng, Fei; Li, Ying; Luo, Xiu-Mei; Tu, Lin; Qu, Jing-Qiu; Xie, Yi-Man; Luo, Yong
Abstract : Icaritin (ICT) is the main component in the traditional Chinese herb Epimedium, and it has been shown to have anti-Alzheimer's disease (AD) effects, but its neuroprotective effects and the pharmacological mechanisms are unclear. In the present study, senescence-accelerated mouse prone 8 (SAMP8) mice were randomly divided into a model group and an ICT-treated group. Learning and memory abilities were detected by the Morris water maze assay, and the expression of amyloid beta protein (A β ) and β -site APP cleavage enzyme 1 (BACE1) was determined by Western blotting and polymerase chain reaction (PCR). Histological changes in CA1 and CA3 were detected by hematoxylin-eosin staining (H&E staining), and the immunohistochemical analysis was used to detect the expression and localization of Bax and Bcl-2. The results showed that compared with the SAMP8 mice, the ICT-treated SAMP8 mice showed improvements in spatial learning and memory retention. In addition, the number of necrotic cells and the morphological changes in CA1 and CA3 areas were significantly alleviated in the group of ICT-treated SAMP8 mice, and the expression of BACE1, A β 1-42 levels, and the Bax/Bcl-2 ratio in the hippocampus was obviously decreased in the ICT-treated group compared with the control group. The results demonstrated that ICT reduced BACE-1 levels, the contents of A β 1-42, and the Bax/Bcl-2 ratio, suggesting that ICT might have potential therapeutic benefits by delaying or modifying the progression of AD.